The wines of Canada - Phillips, Roderick (Infinite Ideas classic wine library., 2017)
Canadian wine expert Rod Phillips provides an overview of Canada's wine regions (British Columbia, Ontario, Quebec and Atlantic Canada), their climate, soil and other geographic conditions, and the grape varieties they grow. He discusses the key producers of each region, as well as analysing vintage variation and noteworthy winemaking techniques.